MENGISI POLA GAMBAR DENGAN TEKNIK KOLASE MELALUI METODE PEMBERIAN TUGAS UNTUK MENINGKATKAN KEMAMPUAN MOTORIK HALUS PADA PESERTA DIDIK DI PAUD NEGERI PEMBINA KEC. RENGAT BARAT - Endang Widia (FIP Unimed, 2016)
ABSTRACT Motor learning success can be achieved if teaching and learning takes place in a fun because that way the child's motivation will arise / rise up so that children have a strong curiosity and passion for learning. In the normal practice of collage, fine motor has not seemed to progress as they only use demonstration method in teaching. Kids less indicates a change in attitude since it tends to be passive and accept what the teacher so that the results obtained are less than the maximum. Therefore, the researcher trying to dig a way to teach learning fill pattern image with collage technique through the method of administration tasks can improve fine motor learners Group B TK Negeri Pembina Rengat District of West. In this PTK in the second cycle of activities